Intraventricular CARv3-TEAM-E T Cells in Recurrent Glioblastoma - Choi, Bryan D.; Gerstner, Elizabeth R.; Frigault, Matthew J.; Leick, Mark B.; Mount, Christopher W.; Balaj, Leonora; Nikiforow, Sarah; Carter, Bob S.; Curry, William T.; Gallagher, Kathleen; Maus, Marcela V. (The New England journal of medicine, 2024)
In this first-in-human, investigator-initiated, open-label study, three participants with recurrent glioblastoma were treated with CARv3-TEAM-E T cells, which are chimeric antigen receptor (CAR) T cells engineered to target the epidermal growth factor receptor (EGFR) variant III tumor-specific antigen, as well as the wild-type EGFR protein, through secretion of a T-cell–engaging antibody molecule (TEAM). Treatment with CARv3-TEAM-E T cells did not result in adverse events greater than grade 3 or dose-limiting toxic effects. Radiographic tumor regression was dramatic and rapid, occurring within days after receipt of a single intraventricular infusion, but the responses were transient in two of the three participants. (Funded by Gateway for Cancer Research and others; INCIPIENT ClinicalTrials.gov number, NCT05660369 .) A novel CAR T-cell therapy directed at EGFRvIII with a secretable EGFR T-cell engager produced rapid responses in three patients with recurrent glioblastoma, but the responses were transient in two of the three.